2020
DOI: 10.3389/fphar.2020.00509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medication Use Pattern Among Patients Presenting to the Emergency Department of Hiwot Fana Specialized University Hospital, Using WHO Prescribing Indicators

Abstract: Background: Ensuring rational drug use requires ongoing evaluation of drug prescribing, dispensing, and use by patients. Health care providers working in an emergency department face unique challenges, including making urgent decisions, patient overload, and limited resources, which contribute to inappropriate drug use. Rational medication use should be an important aspect of emergency care to improve patient outcomes. Thus, this study was conducted to assess medication utilization patterns using World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…[7] Similar to our results, many studies from distinct countries reported higher values than WHO ideal ranges, differing from 2.36 to 5.79. [13,15,16,[22][23][24][25][26] Polypharmacy was significantly higher in patients aged ≥65 years (average number of drugs per prescription: 3.1) than young adults aged between 18 and 44 years (p=0.001). This is an anticipated result due to the increased number of drugs used by increasing age related to existing comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Similar to our results, many studies from distinct countries reported higher values than WHO ideal ranges, differing from 2.36 to 5.79. [13,15,16,[22][23][24][25][26] Polypharmacy was significantly higher in patients aged ≥65 years (average number of drugs per prescription: 3.1) than young adults aged between 18 and 44 years (p=0.001). This is an anticipated result due to the increased number of drugs used by increasing age related to existing comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Drug therapy, which is a crucial part of providing healthcare, is extremely important for the diagnosis, treatment, and management of diseases. 1 However, using medications improperly could cause issues with drug therapy problems (DTPs). DTPs, which are undesirable events experienced by patients related to drug treatment, interfere with achieving the desired goals of the pharmacological intervention and require professional and expert decision-making to resolve.…”
Section: Introductionmentioning
confidence: 99%
“…Medication therapy is the most common therapeutic intervention ( World Health Organization, 2019 ). Medicines management is the process of the evaluation of the patient’s health status and the need for medications’ prescription and dispensing, and the administration and monitoring of medication’s effectiveness ( Car et al, 2017 ; Mishore et al, 2020 ). Medication errors are significantly prevalent and happen in up to 67% of patients during hospitalization ( Nguyen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%